Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Literasi Sains Pada Tema Pencemaran Lingkungan (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2022)
This article explains the influence of the Problem-based Learning (PBL) model on students scientific literacy skills on the theme of environmental pollution. The research used was a quasi-experimental design with a non-equivalent control group. The respondesnts of the study involved one teacher and 22 students. Data on students’scientific literacy abilities were obtained from the pretest and posttest, the analyzed by using SPSS 28.0 for the Windows version. After utilizing normality and homogeneity test, the control and experimental classes were determined to have a reguler and homogenous distribution. The hypothesis was tested by using the Independent Sample t-test in the study. The findings indicated a signifinace value of 0.001<0.05, which indicates that H0 was rejected H1 was accepted. It could be described that there was a statistically significant difference in values between the experimental class the utilized the PBL model and the cotrol class that did Discovery Learning model. According to the data analysis, the PBL model has an influence on students scientific literacy skills on the theme of environmental pollution. Thus, the authors recommended that teachers may iclude the PBL model in their classroom instruction.